(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article provides a comprehensive study of sociolinguistics, its contemporary significance, and the concepts of social status and role within society, illustrating these aspects through the speech of characters in Abdulla Khakhhor’s short stories.